The role of government economic programmes in developing small and medium enterprises in the Sultanate of Oman / Mubarak Ibrahim Adam Mohammad - Mohammad, Mubarak Ibrahim Adam (2014)
It has been stated that government and market forces remain relevant in the development of the economy. Meanwhile, the uncertainty in the global business environment had continued to stimulate activities in the SME sector to the extent that both the Sultanate of Oman and SME owners in the sector have evolved policies that had helped them weather the storm of the business environment. Therefore this study examines the extent to which government assistance influences the development of small and medium size enterprises (SMEs) in the Sultanate of Oman. With a calculated sample size of 885, questionnaires were distributed and 500 valid questionnaires were eventually used for this study. Through the analysis of the questionnaire which is based on a 5-point Likert scale, the study applied correlation and regression analysis for the evaluation of the four research hypothesis of the study. The results showed that government assistance, the study revealed that with exception of financial assistance, the main purposes of all other forms of government assistance were not clear to the SME owners. There is evidence that as the operational constraints (cost of financing, access to finance, license and permits) are reduced, there will be increase in performance in terms of sales growth while the combination of three government assistances (Financial, market and technical assistances) is reported to increase performance in terms of sales growth. Furthermore, the respondents were of the view that government intervention in terms of financial assistance was not enough to meet the needs of the SMEs. Overall, three theories were expounded with the research, namely, that the application of all the six assistance is necessary in order to effectively increase the growth of an SME in terms of sales and profit. Secondly, that only the proper application of the six government assistance will lead to growth of the SMEs in terms of sales and profit and thirdly, that if the government assistance is not properly designed to target specific constraints, there will be no growth of the SME in terms of sales and profit. The study therefore recommended that the creation of an enabling policy environment to facilitate the growth of SMEs through the promotion of strategic alliance, creating public-private partnership, and cooperatives will be effective in helping the SMEs navigate the precarious business environment.